Are our voices heard? Indigenous cultural radio. An experience in Mexico - Cornejo Portugal, Inés (1993)
In this essay the results of the investigations carried out during 1990 and 1991 in the areas of influence of the indigenist radio stations are presented: "La voz de Chinantla", Oaxaca (XEOJN); "The Voice of the Huastecas", San Luis de Potosí (XEANT), and "The Voice of the Mountain", Guerrero (XEZV), which constitute an exploratory approach to the cultural consumption of the media in the coverage of the aforementioned stations, as well as revealing the reception habits of the radio audience. It should be noted that the study was developed from the receiver's perspective; for this reason, the work does not specifically account for the offer of the media, but rather tries to approach cultural consumption based on topics such as ownership of radio and television, seniority in the possession of the medium.